MULTICENTRIC SPINAL CORD AND BRAIN GLIOBLASTOMA: A CASE REPORT - Stanojević, Bojan; Ilić, Jovan; Igić, Aleksandar; Nikolov, Vesna; Aracki-Trenkic, Aleksandra; Đorđević, Marija; Živković, Slavko; Todorović, Stefan (Acta medicae Medianae, 2022)
Multicentric glioblastomas, which simultaneously involve supra- and infratentorial areas, are rare. In our patient, the magnetic resonance imaging (MRI) of cervical and thoracic spine was performed, which verified the spinal intramedullary tumor at the level of the C6 and from Th1 to Th4 segment. During surgery, the tumor, which had macroscopic characteristics of glioblastoma was encountered and it was partially resected. Pathohistological findings verified that the tumor was IDH-wild type glioblastoma. The MRI of the brain was performed after surgery, which showed the right temporoparietal glioblastoma. The patient underwent the postoperative chemoradiation therapy and came for regular check-up examinations for 6 months, however, the patient's neurological signs and symptoms have gradually worsened to this day. Although diagnostic advancements in neuro-oncology have led to more sensitive and specific diagnosis of multicentric gliomas, this topic is still insufficiently researched and requires our attention.
Keywords: glioblastoma, surgical oncology, neurosurgery